Bibliometric study of research in aeronautics, cyberspace, and space exploration for the Colombian Aerospace Force - Ignacio Alfonso Alvarado-Ortega; Nubia Yaneth Gómez-Velasco; Julieth Katherine Rodríguez-Gutiérrez (Revista Científica General José María Córdova)
This bibliometric study addresses the dynamics of publication in three thematic areas relevant to the development of the aerospace sector of the Colombian Aerospace Force, such as aeronautics, space, and cyberspace. The aim is to identify the thematic trends and research emphases published in 2000-2023 and made visible in the Scopus database. The information was analyzed globally and for short intervals with tools such as VoSviewer, identifying thematic clusters based on the co-occurrence of terms and trends of emphasis in different topics. A transition towards multidisciplinary and technologically advanced approaches in aeronautics, cyberspace, and space exploration was evidenced, highlighting their impact on improving research and development practices and strategies within these critical fields.